Rethinking the Call for a US National Data Center in the 1960s: Privacy, Social Science Research and Data Fragmentation Viewed from the Perspective of Contemporary Archival Theory. - Loughnane, Christopher; Aspray, William (Information & Culture, 2018)
This article reconsiders from current archival perspectives the debate surrounding the failed proposal for a national data center in the 1960s. Whereas most accounts of the 1960s effort to construct a national data center in the United States focus on privacy issues, this account focuses more broadly on contextualizing the concerns of the social science community regarding the fragmented state of data archives and on explaining why that moment in particular was a crucial culminating point of sociohistorical and technological pressures in the wider histories of digital computing, archives, data storage and social science scholarship.